Counterterrorism within the Rule of Law? Rhetoric and Reality with Special Reference to the United Kingdom - Walker, Clive (Terrorism and political violence, 2021)
The rule of law remains a hallowed principle even in the unpromising environment of counterterrorism, but failures to live up to rule of law rhetoric must be highlighted. As a result, one might question whether counterterrorism can realistically be conducted wholly in accordance with the rule of law. So, is the rule of law rhetoric or reality? In practice, it remains exceptional for states to resort to express or wide derogations from rule of law standards because of counterterrorism, but notable exceptions in reality undermine the rhetoric of rule of law dominion. By dissecting the rule of law into its constituent components, it is possible to gain a clearer picture of strong and weak points in the rule of law, though no single doctrine, instrument or institution can be found to offer transformational reinforcement. In view of the permanence of counterterrorism, the model required is neither one of accommodation nor an unthinking acceptance of framing ideas such as “the war on terror.” Instead, the rule of law rhetoric demands constant refinement and renewal within the mechanisms of constitutionalism in order to support the reality of rule of law. These precepts will be considered in the context of counterterrorism experiences in the United Kingdom.